2020
DOI: 10.1111/ctr.13780
|View full text |Cite
|
Sign up to set email alerts
|

Going the distance for procurement of donation after circulatory death livers for transplantation—Does reimbursement reflect reality?

Abstract: Donation after circulatory death (DCD) liver transplantation (LT) has increased slowly over the past decade. Given that transplant surgeons generally determine liver offer acceptance, understanding surgeon incentives and disincentives is paramount. The purpose of this study was to assess aggregate travel distance per successful DCD versus deceased after brain death (DBD) liver procurement as a surrogate for surgeon time expenditure and opportunity cost. All consecutive liver offers made to Michigan Medicine fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…One question to be answered is whether transplant centers will be willing to travel substantial distances for DCD livers? A previous single-center study demonstrated that each successful DCD liver procurement required an average of 218 more miles of travel than each successful DBD liver procurement [16]. This difference was largely due to lower successful procurement proportion among DCD procurement episodes.…”
Section: Changes To Allocation and Effects On Dcd Liver Transplantationmentioning
confidence: 99%
“…One question to be answered is whether transplant centers will be willing to travel substantial distances for DCD livers? A previous single-center study demonstrated that each successful DCD liver procurement required an average of 218 more miles of travel than each successful DBD liver procurement [16]. This difference was largely due to lower successful procurement proportion among DCD procurement episodes.…”
Section: Changes To Allocation and Effects On Dcd Liver Transplantationmentioning
confidence: 99%
“…Additionally, appropriate reimbursement for recovery surgeons is necessary in circumstances when the donor fails to progress to circulatory death and the recovery is not performed. This assurance will encourage the participation of experienced surgeons in these DCD recoveries 29 . We hope that this document may lead to the establishment of consistent national practices which may optimize DCD donation potential and the successful utilization of DCD livers for transplantation.…”
Section: Discussionmentioning
confidence: 92%
“…Up to half of all DCD procurements are unsuccessful as donors fail to progress to asystole or WIT exceeds 30 min. A study by the University of Michigan showed that 218 more miles was traveled for each successful DCD liver compared to successful DBD livers, which included miles traveled to donors for both DCD and DBD that were unsuccessful [ 20 ]. These increased travel and opportunity costs are undertaken by the transplant center, which may discourage some centers from aggressively pursuing DCD donors.…”
Section: Discussionmentioning
confidence: 99%